Psychology in equestrian athletes: The rider-horse coordination model - Li, X.; Wang, B.; Ma, H. Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Winning an equestrian competition requires the coordination of the rider and the horse. This subjectdoubled characteristic places increased psychological strain on the athlete. The purpose of this study was to establish a model of "rider-horse coordination" by studying the two-way feedback mechanism between the athlete`s psychology in competition and the horse`s performance, and to develop a theoretical basis for scientific training in the competition. Methods Six sports psychologists, 12 equestrian athletes, four coaches and two veterinarians from the equestrian teams of Shanghai and Mongolia were interviewed. 39 equestrian athletes, eight coaches and four veterinarians from the equestrian teams of Shanghai, Mongolia, Tibet and Guangdong Province completed questionnaires. Separate questionnaires were developed for coaches, athletes and relevant staff based on the research paradigm of Frederick and James. Six valid questionnaires were returned (response rate of 60%). Forty athlete questionnaires were sent out and 39 responded. Five relevant staff questionnaires were sent out and three responded, (recovery rate: 60%). A video analysis was conducted on show-jumping and dressage in the Tenth National Games and the triathlon race of the 2006 National Equestrian Championship. The relationship between athletes` body language and horses` performance was analyzed. The athletes and horses` performance at the moment of success or failure in the competition was recorded as a reference for analyzing the results. During the competitions, athletes` performance, the horses` performance and their obedience, the athletes` performance after success or failure, and the influence on horses were observed and recorded. Results The main factors that influenced the equestrian athletes` mental status were environmental factors and athletes` individual factors. The mental status of the athlete determined their behaviour which in turn influenced the horse`s performance. The horse`s performance also showed a significant influence on the athlete`s mental status. Furthermore, the athlete`s behavior also affected the information transmission. Effective transmission led to success while ineffective transmission led to failure. "Rider-horse coordination" is a process of information transmission between the rider and the horse. This process involves effective control of the horse by the athlete in competition and relies on the horse following the signals sent by the athlete. The achievement of "rider-horse coordination" depends on the athletes` quality, the environment, and the horses` performance. Among these factors, athletes` quality is the base, and horse`s performance is the key, while the environmental condition is the assurance. Discussion / Conclusions Equestrian sports are comprehensive involving physical strength, intelligence, mental effort and willpower. The duality in exercise performance determines the "rider-horse coordination", and it is the key to winning the competition. The results indicated that mental training and psychological consultation and control ensure the athletes` good competitive state. The two-way feedback system and psychological state are two important factors affecting the overall performance. The results suggest that training for both riders and horses requires adequate attention, and the cognition and training of "rider-horse coordination" should be reinforced. This cognitive encoding style will be used in future research to investigate behavioural strategy.